2020
DOI: 10.1111/ddg.14195
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and implications for dermatological and allergological diseases

Abstract: Summary COVID‐19, caused by the coronavirus SARS‐CoV‐2, has become pandemic. A further level of complexity opens up as soon as we look at diseases whose pathogenesis and therapy involve different immunological signaling pathways, which are potentially affected by COVID‐19. Medical treatments must often be reassessed and questioned in connection with this infection. This article summarizes the current knowledge of COVID‐19 in the light of major dermatological and allergological diseases. It identifies medical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 84 publications
(113 reference statements)
1
25
0
15
Order By: Relevance
“…Chronic inflammatory skin diseases such as atopic dermatitis and chronic spontaneous urticaria are commonly treated with systemic immunomodulatory therapy in severe courses, which arises concern about potential risks of COVID-19 infection and vaccination under this systemic therapy [ 21 ].…”
Section: Chronic Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Chronic inflammatory skin diseases such as atopic dermatitis and chronic spontaneous urticaria are commonly treated with systemic immunomodulatory therapy in severe courses, which arises concern about potential risks of COVID-19 infection and vaccination under this systemic therapy [ 21 ].…”
Section: Chronic Inflammatory Skin Diseasesmentioning
confidence: 99%
“…It has been suggested that insult to the nail matrix results in transient growth inhibition with subsequent recovery and thus the appearance of the transverse superficial grooves, usually more marked in the middle aspect of the nail, characteristic of Beau lines [3]. Dermatologic diseases involving different immunological signaling pathways are directly affected by COVID-19 [9]. Similarly, SARS-CoV-2 may itself cause immunological changes, leading to lymphopenia as observed in the described pediatric patients, cytokine storms, and further organ damage [10].…”
Section: Dear Editorsmentioning
confidence: 99%
“…The use of glucocorticoids may predispose patients to a more severe course of COVID-19 [15,18,19]. On the other hand, it was not observed that biological drug therapy also used in AD and psoriasis had similar effects [15,16,18,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%